Major ongoing clinical trials for COVID-19 treatment and studies currently being conducted or scheduled in Japan - Ito, Kyoji (Glob Health Med, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a serious threat to global public health and economies. Currently, hundreds of clinical trials on a wide variety of treatments against COVID-19 are being conducted around the world. Here, we conducted a search for ongoing clinical trials for the treatment of COVID-19 at the clinicaltrials.gov database on April 2, 2020. In total, 48 clinical trials were identified, and of these, 41 trials adopted drug intervention and the other 7 trials utilized biological intervention. The number of trials stratified by a chief country conducting the investigation were 18 in China, 5 in the United States, 4 in Canada, 3 in Italy, 2 in France and Brazil, and 4 trials are being performed multinationally. The drugs utilized in more than one trials were remdesivir (6 trials), lopinavir/ritonavir (6 trials), hydroxychloroquine (6 trials), interferon (5 trials), methylprednisolone (3 trials), nitric oxide gas (3 trials), oseltamivir (2 trials), arbidol (2 trials), and vitamin C (2 trials). We also described the Japanese trials which are now being conducted or scheduled, utilizing lopinavir/ritonavir, remdesivir, favipiravir, ciclesonide and nafamostat.